Women Rights in Islam (Salam International Academic Journal, 2014)
Before Islam, women were deprived and convicted in every sphere of life around the world and were seen wicked and outcast in every part of the world. Even they were deemed inferior than the animals and had no place in the society.With the rise of Islam, ignorance was replaced by the light and happiness ascended around the world. Islam finished every cruelty against women and made here reach her dignified place within the society. Instead of being buried alive she was bestowed with higher status (as a mother) under whom feet the paradise existed and by nurturing her (as a daughter and sister) paradise was attained. Besides, her rights were augmented than the father rights and were to be behaved in a well manner reaching higher position.    In Islam women is given equal rights in every aspect of life and is not deprived of any rights at all. Criticisms on Islam regarding women rights by some people are out of context. One cannot understand the wisdom behind the rights given by Islam unless put it in the whole Islamic context, as Islam is a complete system.Unlike other civilizations, Islam doesn’t deemed women as a utility rather consider her as an honorable human being. Like men, in Islam women are also allowed to work and participate in the society and are to follow and implement Islamic rules. Islam also consider their natural needs and has set rules accordingly. Hence, women in other religions and societies who were victim of cruelty and deemed outcaste, in Islam she was favored with happiness, higher statues and equal rights.
Keywords: Woman; Status; Ignorance (Pre-Islamic); Piety; Rights